Un-Nudging Pay Gaps: The Role of Pay Raise Budget Framing - Gunnell, Hayden T.; Schuhmacher, Karl; Towry, Kristy L. (The Accounting Review, 2026)
ABSTRACT Pay gaps, like gender or racial gaps, violate the widely held belief that employees should receive equal pay for equal work. This study examines whether a common control choice—framing pay raise budgets in percentages—contributes to perpetuating pay gaps. We predict that when the pay raise budget is framed as a percentage (the percentage frame), it inadvertently nudges managers to anchor individual raises on that budget percentage, thereby impounding prior salaries, and thus, existing inequities, into pay raises. We further predict that framing the pay raise budget as an absolute amount (the dollar frame) can un-nudge this behavior. As expected, we find in two experiments that the dollar frame perpetuates pay gaps less than the percentage frame, and that this difference is robust to varying levels of ambiguity about the source of salary differences. Our study examines a simple, cost-effective way to limit the perpetuation of pay gaps. Data Availability: Contact the authors. JEL Classifications: D91; J16; J31; J71; M40; M52.